Policy into practice on sustainable development related teaching in higher education in Turkey - Katayama, Junko; ÖRNEKTEKİN, SERMİN; DEMİR, SIDDIKA SEMAHAT (My University, 2018)
This research explores the current status of implementing policy in sustainable development related teaching in higher education in Turkey. Turkish higher education policy has included increased commitment to sustainable development in recent years. However, there has not been much research conducted on its implementation. Hence, this study involves assessing the current status of sustainable development in teaching at higher education institutions (HEIs) in Turkey. Regarding the research design, a systematic review of accumulated sustainable development related teaching in all 193 HEIs in Turkey (as of the 2015-2016 academic year) was carried out. The accumulated programmes are categorised by occupation concerning sustainable development for the future of Turkey, and the courses are presented within those categories. Whilst many programmes and courses related to sustainable development were identified, the data also reveals the following features: the repetition of same courses; disciplinary partiality, particularly on environmental engineering; disciplinary conservatism and the lack of interdisciplinary practice in general; and last but not least, the differences between what sustainable development means in the European higher education political initiative and what the state of practice is in Turkish higher education.
Keywords: Sustainable Development Teaching; Higher Education; Systematic Review; Turkey; Sürdürülebilir Kalkınma Eğitimi; Yüksek Öğretim; Sistematik İnceleme; Türkiye